The efficacy and safety of laparoscopic common bile duct exploration with primary duct closure for cholecystolithiasis combined with choledocholithiasis - Da Teng; Yue Xu; Qingsong Yang; Wenjun Zhang (Clinical Case Reports)
Key Clinical Message Cholecystolithiasis combined with choledocholithiasis represents a prevalent disease. At present, regarding the management of the common bile duct (CBD), T‐tube drainage (TTD) and primary duct closure (PDC) emerge as two prominent approaches for biliary tract repair after laparoscopic CBD exploration (LCBDE). Here, retrospective analysis was conducted on the clinical records of 157 patients who underwent LCBDE at our hospital between January 2019 and January 2022. All patients were categorized into the PDC group or the TTD group based on the chosen CBD treatment approach. A comparative assessment was made across demographic factors, preoperative conditions, surgical particulars, and postoperative complications. The results showed that PDC is recommended for patients with a limited number of small stones, particularly when the CBD is in the 10–15 mm diameter range.